Faktor-Faktor Yang Mempengaruhi Turnover Intention Karyawan PT Pembangkitan Jawa Bali Services Amurang - Sirait, Tumpal Pangihutan (JURNAL ADMINISTRASI BISNIS (JAB), 2021)
This study aims to analyze the influence factors of turnover intention of the employees of PT Pembangkitan Jawa Bali Services in Amurang, South Minahasa Regency. This research is used quantitative research with survey or questionnaire methods which is intended to provide an overview. Survey method is taken sample from population and uses a questionnaire a means of collecting the main data. There are three types of variables used, independent variables, mediating variables and dependent variables. Workload, work experience and compensation as independent variables, organizational commitment as the mediating variable and turnover intention as the dependent variable. The research involved ninety-one respondents and data processing was analyzed using SmartPLS 3.0. The results showed that workload has positive and significant effect on turnover intention, workload has negative and significant effect on organizational commitment, work experience has negative but insignificant effect on turnover intention, work experience positive and significant effect on organizational commitment, compensation negative but not significant effect. significant on turnover intention, compensation positive and significant effect on organizational commitment, organizational commitment negative but not significant effect on turnover intention.